Literasi Keuangan Digital, Perilaku Konsumtif, Dan Risiko Overborrowing Pada Generasi Z di Era Paylater - Multhazam, Riana; Nurul Fajriah Yahya; Muhammad Qadafi Zulkarnain (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The transformation of the digital financial ecosystem has presented complex challenges for Generation Z in managing personal finances, particularly related to the proliferation of Buy Now Pay Later services. This study analyzes the interconnection between digital financial literacy, consumer behavior, and the risk of overborrowing among 150 Generation Z respondents who are active PayLater users in Makassar City through a quantitative approach with a survey method. The research instrument used a questionnaire compiled with a Likert scale, analyzed using multiple regression. The results show that the level of digital financial literacy of respondents is in the moderate category, while consumer behavior shows a high level. Regression analysis reveals that consumer behavior has a significant positive effect on the risk of overborrowing, while digital financial literacy does not show a significant protective effect. The findings indicate that 58.7 percent of respondents allocate more than 30 percent of their income to installments, with 40.7 percent having active loans on 3-4 platforms simultaneously. This study recommends strengthening holistic financial education that integrates cognitive and behavioral aspects, as well as the implementation of integrated credit scoring regulations to mitigate the systemic risk of overborrowing.